2019
DOI: 10.1007/s13555-019-00324-3
|View full text |Cite
|
Sign up to set email alerts
|

Delusions of Parasitosis: An Update

Abstract: Delusional parasitosis, also known as delusional infestation or Ekbom syndrome, is a relatively infrequent psychotic disorder characterized by an unwavering false belief that there is a parasitic infestation of the skin, despite the absence of any medical evidence that could support this claim. Delusional parasitosis can be categorized into primary, secondary, and organic forms. Sometimes, close relatives also experience identical delusions. This phenomenon was reported to occur in 5–15% of cases, and is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(121 citation statements)
references
References 22 publications
0
112
0
9
Order By: Relevance
“…It has been proposed, by Huber and colleagues, 18 that a decrease in dopamine transport within the striatum, with the consequent rise of its extracellular levels, may contribute to the onset of delusional condition. The above‐mentioned model was supported by Millard and Millard, 19 who proposed that DI may happen in patients with higher dopamine levels, either because of consumption of dopamine transporter inhibitors (cocaine, pemoline, bupropion, amphetamines, among others) or due to secondary disfunction of dopamine transporter (which is observed in traumatic brain injury, Parkinson's disease, schizophrenia, depression, alcoholism, Huntington's disease, human immunodeficiency virus infection, iron deficiency, among others) 19‐21 . It should be noted here that antipsychotics could improve the symptoms of DI in the majority of patients by improving the altered dopamine transmission 1,2,4,5,7‐9,13 …”
Section: Pathophysiologymentioning
confidence: 77%
See 1 more Smart Citation
“…It has been proposed, by Huber and colleagues, 18 that a decrease in dopamine transport within the striatum, with the consequent rise of its extracellular levels, may contribute to the onset of delusional condition. The above‐mentioned model was supported by Millard and Millard, 19 who proposed that DI may happen in patients with higher dopamine levels, either because of consumption of dopamine transporter inhibitors (cocaine, pemoline, bupropion, amphetamines, among others) or due to secondary disfunction of dopamine transporter (which is observed in traumatic brain injury, Parkinson's disease, schizophrenia, depression, alcoholism, Huntington's disease, human immunodeficiency virus infection, iron deficiency, among others) 19‐21 . It should be noted here that antipsychotics could improve the symptoms of DI in the majority of patients by improving the altered dopamine transmission 1,2,4,5,7‐9,13 …”
Section: Pathophysiologymentioning
confidence: 77%
“…Up to 15% of patients can present shared delusional ideas of infestation with a relative or a close friend 21 . This shared psychosis may involve two or more individuals of the family: folie à deux (two people), folie à trois (three), folie à plusieurs o folie à famille (many people or the entire family) 31,32 .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…At present, there is limited understanding concerning the association between DP and medication in the literature, particularly in systematic reviews, case series, and case reports rather than large‐scale case–controlled trials. Antipsychotics, especially second‐generation antipsychotics such as risperidone or olanzapine, are the first choice to manage DP because of their relatively safe profiles and tolerability 1 . In this case, the patient experienced relief after taking olanzapine and had none of the common side‐effects.…”
Section: Figurementioning
confidence: 95%
“…It meets the Diagnostic and Statistical Manual of Mental Disorders , 5th edition, criteria for a delusional disorder. Until now, the literature, including case reports, case series, and systematic reviews, has indicated that antipsychotics that inhibit presynaptic dopamine reuptake at the dopamine transporter are the most effective to treat DP 1 . Serotonergic medications have also been found to be effective 2 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation